2009
DOI: 10.1002/ejic.200900613
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxothiomolybdenum Wheels as Anionic Receptors for Recognition of Sulfate and Sulfonate Anions

Abstract: The formation of supramolecular host–guest cyclic architectures, built up through the self‐condensation process of [Mo2O2S2]2+ oxothiocations driven by sulfate and sulfonate anions is reported. The complexes [(SO4)2Mo10O10S10(OH)10(H2O)5]4– and [(EtSO3)2Mo10O10S10(OH)10(H2O)5]2– were characterized in the solid state by X‐ray diffraction, and particular attention was given to the analysis of the hydrogen‐bonding interactions, which ensure the host–guest stability of such architectures. Taking into account these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…They present applications in catalysis, optics, magnetism, medicine and electrochemistry, among others. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A recently investigated family of POMs is the polyoxovanadoborate (BVO), 21 which presents different vanadium/ boron stoichiometries and different mixed valence V IV /V V ratios. Several frameworks have been reported in the literature with different V/B stoichiometries and in which ethylenediamine and 1,3-diaminopropane, with different degrees of protonation, are present in the crystalline lattice.…”
Section: Introductionmentioning
confidence: 99%
“…They present applications in catalysis, optics, magnetism, medicine and electrochemistry, among others. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] A recently investigated family of POMs is the polyoxovanadoborate (BVO), 21 which presents different vanadium/ boron stoichiometries and different mixed valence V IV /V V ratios. Several frameworks have been reported in the literature with different V/B stoichiometries and in which ethylenediamine and 1,3-diaminopropane, with different degrees of protonation, are present in the crystalline lattice.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the important and in some cases dominant role of hydrogen bonding in the stabilization of host-guest inclusion complexes of ground state guests has been well established and demonstrated in the literature, for a wide range of hosts including cyclodextrins, [23][24][25][26][27][28][29] calixarenes, 30 cucurbiturils, 31,32 and other hosts. [33][34][35] Ross and Rekharsky investigated the quantitative thermodynamic contributions of hydrogen bonding in some specific cyclodextrin inclusion complexes, and reported that a single host-guest hydrogen bond contributes ca. 600 cal mol À1 to the stability (in terms of Gibbs energy) of these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the propensity of the neutral [Mo 10 O 10 S 10 (OH) 10 (H 2 O) 5 ] complex to react with the sulfonate anion prompted us to study the reaction of this compound with a DOWEX anionic resin for which the anchoring sites are paratoluenylsulfonates. This study demonstrates that it is possible to partially graft such Mo‐rings onto the surface of a DOWEX resin, which offers a simple way to immobilize these molecular systems on surfaces 57…”
Section: Ring Design Through Template Effectmentioning
confidence: 89%